2017
DOI: 10.1002/ccr3.861
|View full text |Cite
|
Sign up to set email alerts
|

Acute suppurative thyroiditis in infected thyroid cyst in an adult patient under hemodialysis

Abstract: Key Clinical MessageAcute suppurative thyroiditis (AST) accompanied by an abscess is a rare clinical case. Hemodialysis patients are at risk for infections. Sepsis mortality was from 100 to 300 times higher for chronic dialysis patients than that for the general public. Thus, special care should be taken against infection in patients under hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Sun et al [ 9 ] reported a case of thyroid cyst after fine needle aspiration biopsy (FNAB) complicated by anaerobic bacterial thyroid abscess, surmising that the abscess could have been caused by bacterial contamination from the FNAB process. Igarashi et al [ 10 ] reported a case of acute purulent infection of a thyroid cyst in a hemodialysis patient, speculating that the infection was closely related to bacterial contamination and low systemic immunity during hemodialysis. DM can increase the risk of infection[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [ 9 ] reported a case of thyroid cyst after fine needle aspiration biopsy (FNAB) complicated by anaerobic bacterial thyroid abscess, surmising that the abscess could have been caused by bacterial contamination from the FNAB process. Igarashi et al [ 10 ] reported a case of acute purulent infection of a thyroid cyst in a hemodialysis patient, speculating that the infection was closely related to bacterial contamination and low systemic immunity during hemodialysis. DM can increase the risk of infection[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal duration of IV antibiotic therapy is unclear, with expert opinion recommending 14 days [ 2 ]. Isolated case reports have continued IV antibiotics for up to 37 days, even in patients who demonstrated early response [ 17 ]. As our patient lacked signs of airway compromise and a drainable thyroid abscess, and improved rapidly over the first four days, the decision was made by day 8 to transition her to oral antibiotics and discharge on a 14-day total course.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AST usually occurs in those who have underlying thyroid pathology, such as neoplastic thyroid nodules, Hashimoto's thyroiditis, subacute thyroiditis, multinodular goiters, or penetrating trauma to the thyroid gland [ 2 ]. Cases reported in older adults were associated with degrees of immunocompromisation, such as infection with HIV [ 4 ], renal failure requiring hemodialysis [ 5 ], or reception of stem cell transplant [ 6 ]. Symptoms of AST include fever, dysphagia, and tender neck mass.…”
Section: Discussionmentioning
confidence: 99%